2003
DOI: 10.1563/1548-1336(2003)029<0235:eostps>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sealing the Perforated Sinus Membrane with a Resorbable Collagen Membrane: A Pilot Study in Humans

Abstract: The effects of repairing the perforated sinus membrane with collagen membrane are unknown. The purpose of this pilot study was to clinically, histologically, and histomorphometrically evaluate the results of repairing the perforated sinus membrane with resorbable collagen membrane. A split-mouth design was followed in the current study. Five subjects requiring bilateral sinus grafting were included in the study, where one site was accidentally perforated during sinus augmentation procedures and the other site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
204
0
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(243 citation statements)
references
References 9 publications
8
204
0
12
Order By: Relevance
“…A critical objective of sinus membrane repair is to prevent extravasation of the graft material into the sinus cavity. Schneiderian membrane perforations can be repaired with use of a bioresorbable collagen membrane (Figure 2A) autologous fibrin glue, demineralized freeze-dried human lamellar bone sheet, oxidized regenerated cellulose, sutures and with platelet rich plasma [9,[11][12][13][14][15]17,18,23,30,31,[35][36][37].…”
Section: Management Of the Large Perforated Or Completely Torn Schneimentioning
confidence: 99%
See 2 more Smart Citations
“…A critical objective of sinus membrane repair is to prevent extravasation of the graft material into the sinus cavity. Schneiderian membrane perforations can be repaired with use of a bioresorbable collagen membrane (Figure 2A) autologous fibrin glue, demineralized freeze-dried human lamellar bone sheet, oxidized regenerated cellulose, sutures and with platelet rich plasma [9,[11][12][13][14][15]17,18,23,30,31,[35][36][37].…”
Section: Management Of the Large Perforated Or Completely Torn Schneimentioning
confidence: 99%
“…The most common intraoperative complication reported with grafting of the maxillary sinus is a perforation of the Schneiderian membrane ( Figure 1) that is often managed at the time the perforation is observed [10][11][12][13][14][15][16][17][18]. The incidence of sinus membrane perforation reported in the literature ranges from 7 to 56% [10,11,12,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane perforations can lead to the loss of graft particles into the air chamber of the sinus and have a reported incidence of 10% to 56% (Fugazzotto & Vlassis, 2003;Jensen et al, 1994;Pikos, 2008;Shlomi et al, 2004;van den Bergh et al, 2000;Wallace et al, 2007). A split-mouth study of perforated sinus membrane repair with a resorbable collagen membrane (Proussaefs et al, 2004) found that when bone particles were use, nonperforated sites demonstrated significantly more bone formation (33.58%) than perforated sites (14.17%), with a higher implant survival rate at second-stage surgery (100% vs 69.56%). The authors suggested that the technique or materials be changed to lessen the risk posed by perforation and repair of the sinus membrane.…”
Section: Complicationsmentioning
confidence: 99%
“…Rezorbe olabilen kollajen membranlar, fibrin yapıştırıcılar, sütur ve bukkal yağ grefti uygulamaları membran tamirinde önerilen yöntemlerdendir. [8][9][10] Trombositten zengin fibrin (TZF) ilk defa Choukroun ve ark. …”
Section: Introductionunclassified